PI-Like Fuzzy Logic Direct Torque Control of Permanent Magnet Synchronous Motor (International Journal of Current Engineering and Technology, 2014)
In this paper, the modeling of the Direct Torque Control (DTC) system of permanent magnet synchronous motor (PMSM) based on Matlab/Simulink environment is presented. Simulation results are introduced to predict the motor drive system performance and the effect of PI-like fuzzy controller parameters on speed response in this system . The simulation results show that the torque ripple can be reduced by narrowing the torque hysteresis loops width.
Keywords: Permanent synchronous motor (PMSM), direct torque control (DTC), PI-like fuzzy controller.